Complete Multilineage CD4 Expression Defect Associated With Warts Due to an Inherited Homozygous CD4 Gene Mutation - Fernandes, Rosa Anita; Perez-Andres, Martin; Blanco, Elena; Jara-Acevedo, Maria; Criado, Ignacio; Almeida, Julia; Botafogo, Vitor; Coutinho, Ines; Paiva, Artur; van Dongen, Jacques J. M.; Orfao, Alberto; Faria, Emilia (Frontiers in Immunology, 2019)
IIdiopathic T-CD4 lymphocytopenia (ICL) is a rare heterogeneous syndrome characterized by opportunistic infections due to reduced CD4 T lymphocytes (<300 cells/uL or <20% of T cells) in the absence of HIV infection and other primary causes of lymphopenia. Molecular testing of ICL has revealed defects in genes not specific to CD4 T-cells, with pleiotropic effects on other cell types. Here we report for the first time an absolute CD4 lymphocytopenia (<0.01 CD4+ T-cells/µL) due to an autosomic recessive CD4 gene mutation that completely abrogates CD4 protein expression on the surface membrane of T cells, monocytes, and dendritic cells. A 45-year-old female born to consanguineous parents consulted because of exuberant, relapsing and treatment-refractory warts in her hands and feet since the age of 10 years, in the absence of other recurrent infections or symptoms. Serological studies were negative for severe infections, including HIV 1/2, HTLV-1, and syphilis, but positive for CMV and EBV. Blood analysis showed absence of CD4+ T-cells (<0.01%) with repeatedly increased counts of B-cells, naïve CD8+ T-lymphocytes, and particularly, CD4/CD8 double-negative (DN) TCR- T-cells (30% of T-cells; 400 cells/uL). Flow cytometric staining of CD4 using monoclonal antibodies directed against 5 different epitopes, located in 2 different domains of the protein, confirmed no cell surface membrane or intracytoplasmic expression of CD4 on T-cells, monocytes and dendritic cells, but normal soluble CD4 plasma levels. DN T-cells showed a phenotypic and functional profile similar to normal CD4+ T cells as regards expression of maturation markers, T-helper and T-regulatory chemokine-receptors, TCRvβ repertoire, and in vitro cytokine production against polyclonal and antigen-specific stimuli. Sequencing of the CD4 gene revealed a homozygous (splicing) mutation affecting the last bp on intron 7-8 leading to deletion of the juxtamembrane and intracellular domains of the protein and complete abrogation of CD4 expression on the cell membrane. These findings support previous studies in CD4 KO mice suggesting that surrogate DN-helper and regulatory T-cells capable of supporting antigen-specific immune responses are produced in the absence of CD4 signaling and point out the need for better understanding the role of CD4 on thymic selection and the immune response.